Persistent Postsurgical Pain: Pathophysiology and Preventative Pharmacologic Considerations. (September 2018) - Richebé, Philippe; Capdevila, Xavier; Rivat, Cyril
Abstract : The development of chronic pain is considered a major complication after surgery. Basic science research in animal models helps us understand the transition from acute to chronic pain by identifying the numerous molecular and cellular changes that occur in the peripheral and central nervous systems. It is now well recognized that inflammation and nerve injury lead to long-term synaptic plasticity that amplifies and also maintains pain signaling, a phenomenon referred to as pain sensitization. In the context of surgery in humans, pain sensitization is both responsible for an increase in postoperative pain via the expression of wound hyperalgesia and considered a critical factor for the development of persistent postsurgical pain. Using specific drugs that block the processes of pain sensitization reduces postoperative pain and prevents the development of persistent postoperative pain. This narrative review of the literature describes clinical investigations evaluating different preventative pharmacologic strategies that are routinely used by anesthesiologists in their daily clinical practices for preventing persistent postoperative pain. Nevertheless, further efforts are needed in both basic and clinical science research to identify preclinical models and novel therapeutics targets. There remains a need for more patient numbers in clinical research, for more reliable data, and for the development of the safest and the most effective strategies to limit the incidence of persistent postoperative pain. Abstract : Persistent postsurgical pain is a major complication postsurgery. Long-lasting neuroplastic changes in the nociceptive system resulting from surgery may support persistent postoperative pain. Anesthesiologists may use available pharmacologic interventions to prevent persistent postoperative pain.